Decadal trends in the exclusive breastfeeding practices among working Indian mothers: a multi-level analysis - Ramnika Aggarwal; Priyanka Garg; Madhur Verma; Priya Bindal; Aditi Aditi; Inderdeep Kaur; Minakshi Rohilla; Rakesh Kakkar (International Breastfeeding Journal)
Abstract Background Exclusive breastfeeding (EBF) is defined as feeding infants only breast milk of the mother or a wet nurse for the first six months, without additional food or liquids except the oral rehydration solution or drops/syrups of vitamins, minerals or medicines. The working status of women in developed countries adversely affects the EBF rates, which calls for an assessment in rapidly developing countries like India. Therefore, the primary aim of the present study is to determine the prevalence of EBF using the data from the National Family Health Surveys (NFHS 3, 4, 5) conducted between 2005 and 06, 2015-16 and 2019-21 to estimate the likelihood EBF according to mothers’ employment status. Methods We did a secondary data analysis of the cross-sectional surveys. Exclusive breastfeeding was the primary dependent variable and defined as the percentage of youngest children under six months exclusively breastfed per last 24 h. The employment status of the mother was the primary independent variable and was coded dichotomously (yes/no). Chi-square analysis assessed the association of EBF with the outcome variable of interest. A multi-level modelling approach has been used for portioning variation in the prevalence of exclusive breastfeeding at different geographical levels. Results From NFHS rounds 3 to 5, the overall prevalence of exclusive breastfeeding was 47.45%, 54.85%, and 64.01% respectively. On segregating the women as per their employment status, the prevalence among employed women was 51.1%, 51.1%, and 60.3%, while in unemployed women the prevalence was 45.9%, 54.8%, and 67.3% respectively. The odds of practising EBF in NFHS-5 doubled since NFHS-3 (Adjusted Odds Ratio: 2; 95% Confidence Interval: 1.08, 3.67). Employed mothers had a significantly lower odds ratio (0.94, 0.91, 0.98) of practising exclusive breastfeeding. The likelihood increased when mothers were exposed to media, had normal BMI, and visited health centres > 4 times during pregnancy. The likelihood decreased in older mothers, birth of infant in a health facility, female gender of the child, and late initiation of breastfeeding. Conclusions The lower prevalence of exclusive breastfeeding among working mothers calls for an urgent need to improve policies around maternity benefits at workplaces.